2017
DOI: 10.1530/erc-16-0225
|View full text |Cite
|
Sign up to set email alerts
|

A review of estrogen receptor/androgen receptor genomics in male breast cancer

Abstract: Male breast cancer is a rare disease, of which little is known. In contrast to female breast cancer, the very vast majority of all cases are positive for estrogen receptor alpha (ERα), implicating the function of this steroid hormone receptor in tumor development and progression. Consequently, adjuvant treatment of male breast cancer revolves around inhibition of ERα. In addition, the androgen receptor (AR) gradually receives more attention as a relevant novel target in breast cancer treatment. Importantly, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 80 publications
(84 reference statements)
0
24
0
2
Order By: Relevance
“…Even though many sites for GATA3, FOXA1, and PR were not shared with ERα, both AR and GR show virtually no unique binding sites with respect to ERα binding. AR has been shown to compensate for ERα in ERα-/AR+ female breast cancers 40 , 44 , however the biological interaction between ERα and AR is relatively unknown in both FBC and MBC 45 . The observed genomic overlap of steroid hormone receptor binding profiles is likely due to the close sequence homology of DNA binding domains between all steroid hormone receptors, which warrants potential competition between them in DNA binding.…”
Section: Discussionmentioning
confidence: 99%
“…Even though many sites for GATA3, FOXA1, and PR were not shared with ERα, both AR and GR show virtually no unique binding sites with respect to ERα binding. AR has been shown to compensate for ERα in ERα-/AR+ female breast cancers 40 , 44 , however the biological interaction between ERα and AR is relatively unknown in both FBC and MBC 45 . The observed genomic overlap of steroid hormone receptor binding profiles is likely due to the close sequence homology of DNA binding domains between all steroid hormone receptors, which warrants potential competition between them in DNA binding.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically for MBC, AR expression has been reported as a positive prognostic marker for overall and disease-free survival [ 32 ]. Notably, AR has also received attention as a valid drug target in MBC patients [ 33 ]. Overall, our data add further evidence to a relevant role of AR in MBC and suggest that methylation status of AR promoter may eventually impact on the clinical management of MBC patients.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that AR is expressed in 60–70% of ER − BC and in approximately 68% of the cases in this research . The AR signalling pathway has a significant role in the proliferation and survival of ER − BCs, and inhibition of AR has a therapeutic value in in‐vitro and in‐vivo models of ER − AR + BC cells . PDEF was first identified as an AR co‐regulator and an activator of prostate‐specific antigen (PSA) in the prostate .…”
Section: Discussionmentioning
confidence: 63%
“…26,27 The AR signalling pathway has a significant role in the proliferation and survival of ER À BCs, and inhibition of AR has a therapeutic value in in-vitro and in-vivo models of ER À AR + BC cells. 28 PDEF was first identified as an AR co-regulator and an activator of prostate-specific antigen (PSA) in the prostate. 9 Duane et al performed genomewide expression analysis of 99 primary BC samples and eight BC cell lines, and found that AR and PDEF were overexpressed in ER À BC.…”
Section: S U R V I V a L A N A L Y S I Smentioning
confidence: 99%